Features of educational trajectories and professional plans of students admitted to the university based on the results of school olympiads - I. A. Aleshkovski; A. T. Gasparishvili; O. V. Krukhmaleva; N. P. Narbut; N. E. Savina (RUDN journal of Sociology)
Today the competition for talents, especially young ones, has intensified. This competition is complicated by the demographic situation in most developed countries, increasing competition in the labor market for “quality” resources, digitalization and the widespread penetration of artificial intelligence technologies. At the same time, preferences for one group of students inevitably give rise to discussions about educational inequality, a balance of social justice and the right to education. However, the group of talented students needs closer attention from society, support and assistance from the university. The article considers achievements, academic performance, motivation, educational and professional plans of Russian students who entered universities as winners and prize-winners of school olympiads and are rightly called talented youth. The empirical basis of the article is the data of the student survey conducted in 2024 (N = 64573); in the sample, a group of those admitted without examinations (based on the results of olympiads) was identified (N=915). As the survey results showed, students admitted to the university based on the results of school olympiads have higher educational demands, are more critical in assessing the quality of education and are more actively involved in academic, scientific and research work during their studies. Professional plans of this group are primarily related to research and education. The identified heterogeneity of students’ priorities requires programs and approaches that allow for the successful implementation of various educational demands, providing high-quality education and developing the necessary professional and personal competencies of future specialists in the interests of society. Universities need to improve work on supporting the talented youth, focusing on an individual approach, targeted involvement in research and maximum use of students’ potential in educational activities and professional development.